Impact Of Mobile Phone Usage On Academic Performance Among Secondary School Students In Taraba State, Nigeria - Rabiu, Haruna; Muhammed, Aisha Indo; Umaru, Yunusa; Ahmed, Hadiza Tukur (European Scientific Journal, ESJ, 2016)
This study employed survey design in investigating the influence of mobile phone usage on academic performance among secondary school student in Jalingo, Taraba State, Nigeria. The sample for the study was 300 respondents selected from the total population of 6,482 respondents. Stratified sampling technique was employed to select the sample. The Mobile Phone Usage Questionnaire (MPUQ) adapted from Twum (2011), Mathematic Achievement Test (MAT) and English Language Achievement test (ELAT), were the instrument used for this study. Data collected were analyzed using mean, standard deviation, t-test and ANOVA to answer the research questions and hypotheses. The finding of this study, revealed that mobile phone usage significantly influence academic performance among male and female senior secondary school students (t = 6.113, P = 0.02), age difference was not a significant factor in mobile phone usage on academic performance among senior secondary school students (f = 6.431, P = 0.022), parent’s occupation was not a significant factor in mobile phone usage on academic performance among senior secondary school students (f = 9.005, p= 0.031) and that the frequency of mobile phone usage does not significantly influence academic performance among male and female senior secondary school students (t = 8.131, p = 0.02). It was recommended that, School psychologists, teachers, school administrators, parents and students should be sensitized on the influence of mobile phone usage on academic performance among secondary school students irrespective of gender and age differences.